Building diversity in the speech-language pathology workforce through a blended online Master of Speech Pathology. (4th May 2022) - Easton, Catherine; Verdon, Sarah; Brown, Lisa; Wilson, Linda
Abstract: Purpose : A lack of diversity in the speech-language pathology profession is widely recognised internationally. The role of speech-language pathology education in reproduction of this homogeneity and as a barrier to diversification is little understood. The potential of blended online education to increase access to education and diversify the speech-language pathology profession is yet to be explored. The purpose of the study was to investigate the profile of students engaging in the first blended online speech-language pathology course in Australia, including motivations for studying, experiences of studying via a blended online mode, and intentions for future practice. Method : Data were collected from 44 students in the first Australian blended online Master of Speech Pathology via an online survey. Quantitative data were analysed using descriptive statistics in SPSS and a content analysis of the qualitative data was conducted using NVivo. Result : With over 92% of participants choosing the course because it was offered online, flexible blended online study provided opportunity for those who would not have otherwise accessed speech-language pathology education, including rural students and those balancing work and home commitments. Participants found face to face elements of the course essential to their learning, but also the most challenging to manage and to fit around other commitments. Participants' ideal work scenarios revealed that 82.9% wished to practice within 50kms of their current location, indicating that provision of tertiary education to people in rural areas is contributing to establishing and retaining a rurally focussed speech-language pathology workforce. Conclusion : Blended online study provides an opportunity to diversify the speech-language profession by providing access to students such as rural students and those balancing work and home commitments with tertiary education. By reducing barriers to studying speech-language pathology, flexible learning is helping address issues of access and equity in service delivery across Australia.